Funkcjonowanie zakładu pracy w aspekcie koncepcji stakeholders - Kozłowska, Urszlula (MITEL, 2004)
Ten artykuł jest próbą wyjaśnienia, w jaki sposób działa w ekosystemie wole-rynku. artykuł zawiera trzy części. Pierwsza część artykułu ukazuje problem transformacji i sposobów dogadania się z nową rzeczywistością, na przykład z przemysłem morskim. W następnej części – znajduje się podstawowy profil koncepcji zainteresowanych stron. W ostatnim punkcie artykułu wykazano próbę wcześniejszego poczęcia z wykorzystaniem w określonych pracach Stoczni Szczecińskiej.

This article is an attempt of explaining how the works exsists in the free-market economy. The article contains three parts. The first part of the article shows the problem of transformation and the ways of getting along with the new reality, for example the sea industry. In the next part – the basic profile of the stakeholders conception is located. In the last point of the article it is shown the attempt of the previous conception using in the definite works as Szczecin Shipyard.
To Function Works in the Varialbe Social Reality and Conception Theory of Stakeholders